2022
DOI: 10.1108/itp-01-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

The influence of remote work communication satisfaction and CSR association on employee alienation and job satisfaction: a moderated-mediation study

Abstract: PurposeScholars and practitioners have raised concerns that mandatory remote work can lead to feelings of isolation and alienation in employees. Therefore, this study aims to investigate this issue by examining the impact of work communication satisfaction in remote environments on employee alienation and job satisfaction.Design/methodology/approachSensemaking and social information processing (SIP) theory are used for formulating the hypotheses. To test the hypotheses, primary data were collected from 418 emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 141 publications
(322 reference statements)
0
12
0
1
Order By: Relevance
“…In order to do this, the researcher came up with long-term strategies that can serve as a foundation for creating comprehensive plans for subsequent product revisions (Basami, 2022). The process included formulating a strategy (Kakkar et al, 2023). An example of a technical tool that can assist managers and decision-makers in making sense of the enormous amounts of information available in online repositories and databases is artificial intelligence .…”
Section: Literature Review and Hypotheses Development Business Intell...mentioning
confidence: 99%
“…In order to do this, the researcher came up with long-term strategies that can serve as a foundation for creating comprehensive plans for subsequent product revisions (Basami, 2022). The process included formulating a strategy (Kakkar et al, 2023). An example of a technical tool that can assist managers and decision-makers in making sense of the enormous amounts of information available in online repositories and databases is artificial intelligence .…”
Section: Literature Review and Hypotheses Development Business Intell...mentioning
confidence: 99%
“…Buna ek olarak işe yabancılaşmanın, çalışanların zihnine yerleşmesi ve operasyonel gerekliliklere otomatik ve sistematik bir yanıt olarak yansıması riski vardır ve bu da hem bireysel performansı hem de kurumsal performansı etkilemektedir (Basten ve Haamann, 2018;Odor, 2018;Özer, Uğurluoğlu, Saygılı ve Sonğur, 2019). Bununla birlikte işe yabancılaşma örgütlerdeki kişiler arası ilişkileri kesintiye uğratmakta, sosyal ağlara katılımı azaltmakta, iş yerinde şüpheye neden olmakta, sosyal ilişkileri zayıflatmakta ve çalışanı sadece memnuniyetsiz değil aynı zamanda işine karşı motivasyonsuz hâle getirmektedir (Shantz, Alfes, Bailey ve Soane, 2015;Gülmez ve Özdemir, 2023;Kakkar, Kuril, Singh, Saha ve Dugar, 2023).…”
Section: Literatür Taraması Ve Hipotez Geliştirmeunclassified
“…Job satisfaction has been a popular topic in both academic and practical research, and it significantly affect various aspects of employee's work related attitude and behavior (Ran et al, 2021). Research has been done on job satisfaction in the context of job performance, employee alienation, authentic leadership, self-efficacy, educational assortative matching, remote work communication, teamwork, optimistic expectations, emotion and beliefs, job crafting, workplace spirituality, organizational citizenship behavior (Bryan & Vitello-Cicciu, 2022;Dubey et al, 2022;Kakkar et al, 2022;Matagi et al, 2022;Poghosyan et al, 2022;Tempieri, 2022;Vettori et al, 2022;Yesilkaya & Yildiz, 2022). For example, the work of Lee et al (2019) provides some evidence of intersectionality, where they found that diversity management and satisfaction on pay are most important to minority women and least important to White men.…”
Section: Job Satisfactionmentioning
confidence: 99%